BMI1 Silencing Induces Mitochondrial Dysfunction in Lung Epithelial Cells Exposed to Hyperoxia - Hernández-Cuervo, Helena; Soundararajan, Ramani; Sidramagowda Patil, Sahebgowda; Breitzig, Mason; Alleyn, Matthew; Galam, Lakshmi; Lockey, Richard; Uversky, Vladimir N.; Kolliputi, Narasaiah (Frontiers in Physiology, 2022)
Acute Lung Injury (ALI), characterized by bilateral pulmonary infiltrates that restrict gas exchange, leads to respiratory failure. It is caused by an innate immune response with white blood cell infiltration of the lungs, the release of cytokines, an increase in reactive oxygen species (ROS), oxidative stress, and changes in mitochondrial function. Mitochondrial alterations, changes in respiration, ATP production, and the unbalancing fusion and fission processes are key events in ALI pathogenesis and increase mitophagy. Research indicates that BMI1 (B cell-specific Moloney murine leukemia virus integration site 1), a protein of the Polycomb repressive complex 1, is a cell cycle and survival regulator that plays a role in mitochondrial function. BMI1-silenced cultured lung epithelial cells were exposed to hyperoxia to determine the role of BMI1 in mitochondrial metabolism. Its expression decreases in human lung epithelial cells (H441) following hyperoxic insult, as determined by western blot, qRT-PCR, and functional analysis. This decrease correlates with an increase in mitophagy proteins, PINK1, Parkin, and DJ1; an increase in the expression of tumor suppressor PTEN; changes in the expression of mitochondrial biomarkers; and decreases in the oxygen consumption rate and tricarboxylic acid enzyme activity. Our bioinformatics analysis suggested that the BMI1 multifunctionality is determined by its high level of intrinsic disorder that defines the ability of this protein to bind to numerous cellular partners. These results demonstrate a close relationship between BMI1 expression and mitochondrial health and indicate that BMI1 is a potential therapeutic target to treat ALI and Acute Respiratory Distress Syndrome.